2019
DOI: 10.1002/mabi.201800346
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Microvascular Networks on Sulfonated Polyrotaxane Surfaces with Immobilized Vascular Endothelial Growth Factor

Abstract: Modulation of material properties and growth factor application are critical in constructing suitable cell culture environments to induce desired cellular functions. Sulfonated polyrotaxane (PRX) surfaces with immobilized vascular endothelial growth factors (VEGFs) are prepared to improve network formation in vascular endothelial cells. Sulfonated PRXs, whereby sulfonated α‐cyclodextrins (α‐CDs) are threaded onto a linear poly(ethylene glycol) chain capped with bulky groups at both terminals, are coated onto s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This suggests that the cells can distinguish differences in the molecular mobility of polyrotaxane surfaces, which is consistent with our previous studies. [35,37] Reportedly, subcellular YAP localization depends on the elastic modulus and surface nanostructure of cell-adhesive substrates. [14,39] As the polystyrene surface coated with a thin layer of SPE-PRX 5 or SPE-PRX 86 was rigid and extremely smooth (Figure S1, Supporting Information), these material parameters are expected to minimally impact cellular YAP localization in the present study.…”
Section: Yap Localization and Proliferation Of Young Huvecs On Polyrotaxane Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the cells can distinguish differences in the molecular mobility of polyrotaxane surfaces, which is consistent with our previous studies. [35,37] Reportedly, subcellular YAP localization depends on the elastic modulus and surface nanostructure of cell-adhesive substrates. [14,39] As the polystyrene surface coated with a thin layer of SPE-PRX 5 or SPE-PRX 86 was rigid and extremely smooth (Figure S1, Supporting Information), these material parameters are expected to minimally impact cellular YAP localization in the present study.…”
Section: Yap Localization and Proliferation Of Young Huvecs On Polyrotaxane Surfacesmentioning
confidence: 99%
“…[29][30][31][32][33][34] We fabricated cell-adhesive surfaces coated with molecularly mobile polyrotaxanes and explored the potential effects of molecular mobility on cellular responses. [29][30][31][32][33][34][35][36][37][38] On culturing various types of cells, such as human umbilical vein endothelial cells (HUVECs), [35] human bone marrow-derived mesenchymal stem cells (HBmMSCs), [36] human hepatomaderived cell line, [37] and mouse Kupffer cell line, [38] polyrotaxane surfaces with high mobility tended to promote cytoplasmic YAP localization in adherent cells, whereas those with low mobility tended to promote nuclear YAP localization. The molecular mobility of polyrotaxane surfaces affects cellular functions, such as stemness, [36] protein secretion, [37] and immune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of microvascular networks in implanted biomaterials is one of the key events for a successful tissue regeneration, as these microvessels are necessary for the efficient transport of cells, nutrients, and removal of the wastes [59]. It was observed that the molecular mobility of PRXs could be used to modulate the formation of microvascular networks [60]. Human umbilical vein endothelial cells (HUVECs) were cultured on VEGFimmobilized S-PRX surfaces, and they respond to different molecular mobility was studied.…”
Section: Prxs For Other Tissue Engineering Applicationsmentioning
confidence: 99%
“…For instance, it has been observed that a variation in matrix stiffness from soft to rigid can direct mesenchymal stem cell (MSC) fate [5]. Apart from this, we have developed cell culture surfaces using supramolecular polymers, polyrotaxanes (PRXs), and succeeded in regulating cellular functions such as adhesion [6], proliferation [7], and differentiation [8]. PRX is a supermolecule consisting of cyclic molecules threaded onto the axis polymer.…”
Section: Introductionmentioning
confidence: 99%